Impact of spawn concentrations on Atlantic herring (Clupea harengus) egg survival in Baltic Sea inshore spawning areas. (30th September 2022) - Finke, Annegret; von Nordheim, Lena; Kotterba, Paul; Polte, Patrick
Abstract: Fish species classified as demersal substrate spawners attach their eggs on macrophytes or hard substratum. As a result of consecutive events of egg deposition and successive waves of spawning adults, the formation of multiple egg layers on spawning substrate was already observed for demersal spawning fish species, such as the Atlantic herring ( Clupea harengus, Linnaeus 1758). However, empirical information on the effects of egg concentration on herring egg survival are scarce. Hypothesizing that high egg concentration has a negative effect on herring egg survival, we experimentally investigated egg mortalities in artificially spawned egg clusters of 1–10 vertical layers. Moreover, potential effects of egg packing density (loose and dense) in one single layer set-up were investigated. We found decreasing herring egg survival in clusters of increasing egg layers. Although egg mortality was lowest in surface layers, a layerwise analysis did not reveal a stepwise increase of egg mortality from outermost to innermost eggs. Furthermore, egg mortality in surface layers significantly increased with increasing egg layer number underneath, indicating that the extent of layering is affecting egg mortality also in surface layers. This implies a reproductive disadvantage not only for eggs being spawned in the beginning of consecutive spawning events but also for latest spawned eggs. However, different egg packing densities in single layer spawn did neither influence the fertilization success nor mortality of herring eggs. Increased thickness of egg layers may result from the ongoing reduction and fragmentation of coastal vegetation due to eutrophication and coastal modifications. Our results indicate that such multiple egg layer deposition has the potential to negatively impact hatching success in demersal spawning fish species, such as the herring. Graphical abstract: Image 1 Highlights: We investigated density-dependent herring egg mortality via laboratory experiments. The total egg mortality increases with the number of layers within batches of spawn. Surface layer mortality is lowest but increases with numbers of egg layers underneath. Monolayers result in best egg survival but require more area of spawning substrate. Habitat loss related increase in spawn concentrations pose a threat for egg survival.